Effect of Nursing Intervention on Mothers' Knowledge of Cervical Cancer and Acceptance of Human Papillomavirus Vaccination for their Adolescent Daughters in Abuja - Nigeria - Funmilola T Odunyemi; Chizoma M Ndikom; O Abimbola Oluwatosin (Elsevier, 2018)
Objective: The aim of this study is to evaluate the effect of nursing intervention on mothers' knowledge of cervical cancer and acceptance of human papillomavirus (HPV) vaccination for their adolescent daughters in Abuja, Nigeria. Methods: This was a quasi-experimental study that utilized two groups pre and post-test design. The study was carried out among civil servant mothers in Bwari (experimental group [EG]) and Kwali (control group[CG]) Area Councils of Abuja, Nigeria. One hundred and forty-six women who met the inclusion criteria were purposively selected for this study. EG consists of 69 women while 77 are from CG. The intervention consisted of two days workshop on cervical cancer and HPV vaccination. Descriptive and inferential analyses of the data were performed using SPSS software 20 version. Results: The mean age of the respondents was 35 years ± 6.6 in the EG and 41 years ± 8.2 in the CG. The mean knowledge score of cervical cancer was low at baseline in both EG (9.58 ± 7.1) and CG (11.61 ± 6.5). However, there was a significant increase to 21.45 ± 6.2 after the intervention in EG (P < 0.0001).The baseline acceptance of HPV vaccination was high in EG after intervention from 74% to 99%. Exposure to nursing intervention and acceptance of HPV vaccination was statistically significant after intervention (P < 0.0001). Conclusions: The nursing intervention has been found to increase mothers' knowledge of cervical cancer and acceptance of HPV vaccination. It is therefore recommended that nurses should use every available opportunity in mothers' clinic to educate on cervical cancer and HPV vaccination.